Hubungan Durasi Hipertensi Terhadap Pola Elektrokardiogram: Kajian Klinis Untuk Deteksi Dini Perubahan Jantung - Marwono, Marwono; Apris, Muh. Asrul; Asri, Muhammad (Madu Jurnal Ilmu Kebidanan, 2025)
Hypertension is a major risk factor contributing to cardiovascular disorders, including left ventricular hypertrophy, making early detection through an ECG crucial for preventing complications. This study aimed to assess the relationship between hypertension duration and LVH/RVH findings and the overall interpretation of the ECG.The method used was a clinical experiment with a quantitative approach involving 67 hypertensive patients with disease duration of ≤5 years and >5 years. ECG data were analyzed to identify changes in patterns related to hypertension duration, and the Pearson correlation test was used to assess the relationship between variables. The sample was predominantly adult to elderly and predominantly female, with a relatively balanced distribution of hypertension duration. The analysis revealed a significant negative association between hypertension duration and LVH/RVH findings (r = –0.255; p = 0.038) and a weak but significant positive association between hypertension duration and overall ECG abnormalities (r = 0.285; p = 0.020). This pattern indicates that although cardiac structural and electrical changes tend to increase with hypertension duration, the limited sensitivity of the ECG results in a non-linear relationship. This study concludes that hypertension duration is associated with ECG changes, although the strength is weak, necessitating additional evaluation for a comprehensive cardiac assessment.